2015
DOI: 10.1245/s10434-015-4697-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Molecular Subtype and Residual Disease on Locoregional Recurrence in Breast Cancer Patients Treated with Neoadjuvant Chemotherapy and Postmastectomy Radiation

Abstract: Background The relative contribution of biologic subtype to locoregional recurrence (LRR) in patients who have been treated with neoadjuvant chemotherapy (NAC), mastectomy and postmastectomy radiotherapy (PMRT) is not clearly defined. Methods 233 patients with Stage II-III breast cancer received NAC, mastectomy and PMRT between 2000-2009: 53% (n=123) had HR+ (ER or PR+/HER2−), 23% (n=53) had HER2+ (HER2+/HR+ or HR−), and 24% (n=57) had triple negative disease (TN: HR−/HER2−). The 5-year LRR rates were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 17 publications
(16 reference statements)
1
27
1
Order By: Relevance
“…A prior small study that included 53 patients with HER2-positive disease demonstrated favorable locoregional recurrence rates regardless of response to neoadjuvant chemotherapy. [26] The findings from this study and the current study are in contrast to multiple previous studies which have shown that in patients with HER2-positive disease pCR is associated with improved survival compared to those with residual disease. [7, 11, 13, 33, 35] A meta-analysis of studies by Cortazar et al which included 1989 patients with HER2-positive disease showed a significant difference in event-free survival between the 586 patients who achieved a pCR and the 1403 patients with residual disease.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A prior small study that included 53 patients with HER2-positive disease demonstrated favorable locoregional recurrence rates regardless of response to neoadjuvant chemotherapy. [26] The findings from this study and the current study are in contrast to multiple previous studies which have shown that in patients with HER2-positive disease pCR is associated with improved survival compared to those with residual disease. [7, 11, 13, 33, 35] A meta-analysis of studies by Cortazar et al which included 1989 patients with HER2-positive disease showed a significant difference in event-free survival between the 586 patients who achieved a pCR and the 1403 patients with residual disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with other studies, we found that patients with TNBC that achieved a pCR had a significantly better BCSS and OS compared with those with residual disease. [26] In fact, patients with TNBC who experienced a pCR had 5-year BCSS and OS in keeping with the other tumor subtypes. It is reassuring that such patients with “chemosensitive” TNBC, have an excellent outcome, such that additional systemic therapy may not be necessary.…”
Section: Discussionmentioning
confidence: 80%
“…The relationship between LRR, response to NAC, and breast cancer subtype has been described in a few large single-institution studies and a meta-analysis (17,(72)(73)(74). A large study of 751 breast cancer patients (219 with TNBC) by the MD Anderson Cancer Center group showed that TNBC patients treated with NAC not only had a high pCR rate compared with the HRþ/HER2À patients (42% vs 16.5%, respectively) but also that survival outcomes differed among TNBC patients according to chemotherapy response (17).…”
Section: Locoregional Control For Patients With Tnbc Undergoing Nacmentioning
confidence: 99%
“…Another large analysis of the European Organisation for Research and Treatment of Cancer (EORTC) 10994/BIG 1 − 00 study of patients with locally advanced breast cancer receiving NAC showed that pCR was a favorable factor with regards to the prediction of LRR after NAC [16]. Several retrospective series also demonstrated that achieving pCR after NAC can result in better local control following surgery [1][2][17][18]. Therefore, achieving pCR was an important factor not only for distant disease control but also for local control.…”
Section: Discussionmentioning
confidence: 99%